Identification of drug candidates targeting monocyte reprogramming in people living with HIV - Knoll, Rainer; Bonaguro, Lorenzo; dos Santos, Jéssica C.; Warnat-Herresthal, Stefanie; Jacobs-Cleophas, Maartje C. P.; Blümel, Edda; Reusch, Nico; Horne, Arik; Herbert, Miriam; Nuesch-Germano, Melanie; Otten, Twan; van der Heijden, Wouter A.; et al. (Frontiers in Immunology, 2023)
We have previously illustrated in a cross-sectional cohort study that people living with HIV (PLHIV) are characterized by functional reprogramming of innate immune cells (van der Heijden et al., 2021a). In order to assess technical feasibility of omics technologies for application to larger cohorts, we compared bulk and single-cell transcriptomics as well as chromatin landscape analysis by ATAC-seq in a small number of blood samples derived from PLHIV and healthy controls from the 200-HIV cohort study. In particular, 1) single-cell RNAseq analysis revealed that most immune cells in peripheral blood of PLHIV are altered in their transcriptomes, 2) that a specific functional monocyte state previously described in acute HIV infection is still existing in PLHIV while other monocyte cell states are only occurring in acute HIV, and 3) that a reverse transcriptome approach on a rather small number of PLHIV is sufficient to identify drug candidates for reversing the transcriptional phenotype of monocytes in PLHIV. These scientific findings and technological advancements for clinical application of single-cell transcriptomics form the basis for the larger 2000-HIV multicenter cohort study on PLHIV (Vos et al., 2022), for which a combination of bulk and single-cell transcriptomics will be included as the leading technology to determine disease endotypes in PLHIV and to predict disease trajectories and outcomes.